2011
DOI: 10.4103/1119-3077.84000
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems of siblings of epileptic children in Enugu

Abstract: Siblings of children with epilepsy have more behavioral disturbances than controls. A strong association was found between poor seizure control and the prevalence of behavioral problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…There appeared to be a broader contribution of family relatedness to measures of social competence and behavioral problems. Consistent with the literature that has compared children with epilepsy to either siblings or healthy controls, lower competence and higher total behavioral problems were evident in the children with epilepsy compared with both unaffected siblings and typically developing controls (Aronu & Iloeje, 2011;Austin et al, 2001). However, unaffected siblings exhibited significantly lower competence and higher behavioral problems compared to the controls, consistent with more recent findings suggesting a contribution of family relatedness, reflecting an impact of genetic, social, or other factors (Hesdorffer et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…There appeared to be a broader contribution of family relatedness to measures of social competence and behavioral problems. Consistent with the literature that has compared children with epilepsy to either siblings or healthy controls, lower competence and higher total behavioral problems were evident in the children with epilepsy compared with both unaffected siblings and typically developing controls (Aronu & Iloeje, 2011;Austin et al, 2001). However, unaffected siblings exhibited significantly lower competence and higher behavioral problems compared to the controls, consistent with more recent findings suggesting a contribution of family relatedness, reflecting an impact of genetic, social, or other factors (Hesdorffer et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…This bidirectional relationship has been reported for a variety of comorbid conditions including depression, suicidality, ASD, ADHD, psychosis, and schizophrenia (Lin, Mula, & Hermann, 2012). Not only are there shared susceptibilities between epilepsy and specific behavioral comorbidities, but of particular interest is evidence of co-aggregation of cognitive, behavioral, and even brain structural abnormalities in the siblings and parents of persons with epilepsy compared to general population controls (Alhusaini et al, 2015; Aronu & Iloeje, 2011; Badawy, Vogrin, Lai, & Cook, 2013; Chowdhury et al, 2014; Hesdorffer, Caplan, & Berg, 2012; Iqbal et al, 2015; Iqbal et al, 2009; Singhi, Bansal, Singhi, & Pershad, 1992; Tsai et al, 2013; Verrotti et al, 2013; Wandschneider et al, 2014; Wandschneider et al, 2010). These observations suggest the presence of distinct endophenotypes underlying epilepsy and some of its comorbidities, suggesting possible shared genetic mechanisms, although the influence of environmental factors remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that they are more prone to psychiatric and emotional problems than parents and siblings of children without seizure disorder. [11,12] For these reasons, children with seizure disorder are likely to be withdrawn from school either by their parents or the school authorities. For those who still go to school in spite of the stigmatization, their academic performance is lower than that of children without seizure disorder.…”
Section: Introductionmentioning
confidence: 99%